2021
DOI: 10.1001/jamacardio.2021.0379
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dapagliflozin in Men and Women With Heart Failure With Reduced Ejection Fraction

Abstract: IMPORTANCEWomen may respond differently to certain treatments for heart failure (HF) with reduced ejection fraction (HFrEF) than men.OBJECTIVE To investigate the efficacy and safety of dapagliflozin compared with placebo in men and women with HFrEF enrolled in the Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure trial (DAPA-HF).DESIGN, SETTING, AND PARTICIPANTS Prespecified subgroup analysis of a phase 3 randomized clinical trial conducted at 410 sites in 20 countries. Patients with New York H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 61 publications
4
21
1
Order By: Relevance
“…A total of 4744 patients (1109 women [23.4%]; 3635 men [76.6%]) were randomized in DAPA-HF, with a mean (SD) age of 66.3 (10.9) years (eFigure 2 in Supplement 2). Baseline demographic characteristics of the study population have been previously reported . The distribution of age at randomization and at the time of a primary composite end point and death from any cause are shown in eFigure 3 in Supplement 2.…”
Section: Resultscontrasting
confidence: 55%
“…A total of 4744 patients (1109 women [23.4%]; 3635 men [76.6%]) were randomized in DAPA-HF, with a mean (SD) age of 66.3 (10.9) years (eFigure 2 in Supplement 2). Baseline demographic characteristics of the study population have been previously reported . The distribution of age at randomization and at the time of a primary composite end point and death from any cause are shown in eFigure 3 in Supplement 2.…”
Section: Resultscontrasting
confidence: 55%
“…21–24 This is expected as women more often have HFrEF due to nonischemic causes than men. 2,8 The present analysis demonstrated substantial differences in the clinical profile between sexes, most of which confirmed known sex differences in HFrEF. 2,7,8 An interesting finding was the significantly higher proportion of women who had a CRT device.…”
Section: Discussionsupporting
confidence: 81%
“…2,8 The present analysis demonstrated substantial differences in the clinical profile between sexes, most of which confirmed known sex differences in HFrEF. 2,7,8 An interesting finding was the significantly higher proportion of women who had a CRT device. The high use of CRT in women is particularly striking because they seem to derive greater benefit from this therapy than men.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In general, the effect of dapagliflozin on the primary composite endpoint was consistent across numerous prespecified patient subgroups, including age (≤ 65 vs > 65 years), body mass index (BMI; < 30 vs ≥ 30 kg/ m 2 ), LVEF (≤ vs > median), and NT-proBNP level (≤ vs > median) [13]. In prespecified analyses, dapagliflozin significantly reduced the risk of worsening HF or CV death regardless of gender [19], presence of T2DM [20], MRA use [21], etiology (ischemic vs non-ischemic HF) [22], and eGFR (< 60 vs ≥ 60 mL/min/1.73 m 2 ) [23]. In an exploratory analysis, dapagliflozin increased event-free survival from a primary composite event by 2.1 years for a patient aged 65 years [24].…”
Section: Worsening Heart Failure or Cardiovascular Deathmentioning
confidence: 88%